DolFin: an innovative digital platform for studying Risso's dolphins in the Northern Ionian Sea (North-eastern Central Mediterranean). Issue 1 (December 2018) - Maglietta, Rosalia; Renò, Vito; Cipriano, Giulia; Fanizza, Carmelo; Milella, Annalisa; Stella, Ettore; Carlucci, Roberto
Abstract The Risso's dolphin is a widely distributed species, found in deep temperate and tropical waters. Estimates of its abundance are available in a few regions, details of its distribution are lacking, and its status in the Mediterranean Sea is ranked as Data Deficient by the IUCN Red List. In this paper, a synergy between bio-ecological analysis and innovative strategies has been applied to construct a digital platform, DolFin . It contains a collection of sighting data and geo-referred photos ofGrampus griseus, acquired from 2013 to 2016 in the Gulf of Taranto (Northern Ionian Sea, North-eastern Central Mediterranean Sea), and the first automated tool forSmart Photo Identification of the Risso's dolphin (SPIR ). This approach provides the capability to collect and analyse significant amounts of data acquired over wide areas and extended periods of time. This effort establishes the baseline for future large-scale studies, essential to providing further information on the distribution ofG. griseus . Our data and analysis results corroborate the hypothesis of a resident Risso's dolphin population in the Gulf of Taranto, showing site fidelity in a relatively restricted area characterized by a steep slope to around 800 m in depth, north of the Taranto Valley canyon system.